Exploitation of heterosis in a diallel crosses of periwinkle (Catharanthus roseus) for morphological traits - RAVIKUMAR, BOLAGAM; DHATT, K K (The Indian Journal of Agricultural Sciences, 2023)
Despite the economic significance of periwinkle [Catharanthus roseus (L.) G. Don] the existence of genetic variation in traits have been largely unexplored and very little attempt has been done to improve its genetics for ornamental prospective. An experiment was conducted at the research farm of Punjab Agricultural University, Ludhiana, Punjab during 2019 to 2021 using 6 inbred lines of periwinkle to develop 30 F1 populations in full-diallel fashion. The highly significant positive heterobeltiosis was recorded in the progeny of Vi-29 × Vi-14-3 for leaf breadth, follicle length, number of flowers per plant and number of seeds per follicle. The cross combination Vi-13-2 × Vi-29 was recorded significantly high heterobeltiosis for plant height and plant spread. The minimum heterobeltiosis was recorded for plant spread and follicle length in cross Vi-14-3 × Vi-15-1. The highest mean performance of the parents reported in Vi-15-1 for plant spread, internode length, flower diameter, number of flowers per plant, follicle length and number of seeds per follicle. As per the results among the cross combinations superior mean performance was observed in the Vi-15-1 × Vi-14-3 for leaf length and number of flowers per plant. These findings suggest that hybridization is an efficient way of contributing genetic variability in periwinkle for landscape utilization.